2016
DOI: 10.1182/bloodadvances.2016000372
|View full text |Cite
|
Sign up to set email alerts
|

YY1 controls Eμ-3′RR DNA loop formation and immunoglobulin heavy chain class switch recombination

Abstract: Key Points Transcription factor YY1 regulates the IgH Eμ-3′RR long-distance DNA loop without the YY1 transcriptional activation domain. YY1 constructs that rescue the Eμ-3′RR DNA loop also restore CSR strongly arguing for the necessity of this long-distance DNA loop for CSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 25 publications
(27 reference statements)
0
30
0
Order By: Relevance
“…The YY1 protein can also bind RNA [ 25 , 26 ], and the Repeat C region of Xist contains three YY1 binding sites required for tethering Xist RNA to the chromatin of the Xi in post-XCI somatic cells [ 27 ]. YY1 mediates the long-distance DNA interactions required for V(D)J recombination of the immunoglobulin loci and for class switch recombination, and B cell specific YY1 deletion arrests B cell development at the pro-B cell stage [ 28 32 ]. We recently found that YY1 deletion or disruption in activated female T and B cells disrupts Xist RNA localization to the Xi with minimal impact on Xist expression [ 33 ], suggesting that YY1 may regulate XCI maintenance through mediating Xist RNA localization in lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The YY1 protein can also bind RNA [ 25 , 26 ], and the Repeat C region of Xist contains three YY1 binding sites required for tethering Xist RNA to the chromatin of the Xi in post-XCI somatic cells [ 27 ]. YY1 mediates the long-distance DNA interactions required for V(D)J recombination of the immunoglobulin loci and for class switch recombination, and B cell specific YY1 deletion arrests B cell development at the pro-B cell stage [ 28 32 ]. We recently found that YY1 deletion or disruption in activated female T and B cells disrupts Xist RNA localization to the Xi with minimal impact on Xist expression [ 33 ], suggesting that YY1 may regulate XCI maintenance through mediating Xist RNA localization in lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Several key NPC-specific enhancer-gene looping interactions were ablated upon Yy1 knockdown. YY1 is an intriguing architectural protein candidate: (1) it is strongly enriched in genome-wide looping interactions in human cell lines (Rao et al 2014); (2) it is necessary for the formation of specific 3D interactions in B cells (Medvedovic et al 2013); (3) it can connect a long-range interaction in B cells in the absence of its transcriptional activation domain (Mehra et al 2016); and (4) it is required for proper neural development (He et al 2007). Future studies should aim to elucidate YY1's function as an architectural protein in non-neural lineages and determine the extent to which YY1's critical role in looping is due to indirect effects on chromatin activity.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…Specifically, we found that YY1 conditional knock-out ablates the long-distance 220kb DNA loop between the Eμ and 3'RR enhancers believed to be necessary for CSR [43]. We further showed that the YY1 C-terminal half which lacks the transcriptional activation domain is sufficient for controlling this loop [43]. These results indicate that YY1 impacts B cell function by numerous mechanisms including control of gene expression, long-distance DNA loops, and AID stability and nuclear function.…”
Section: Discussionmentioning
confidence: 76%
“…However, we recently found that YY1 also controls other functions that impact CSR. Specifically, we found that YY1 conditional knock-out ablates the long-distance 220kb DNA loop between the Eμ and 3'RR enhancers believed to be necessary for CSR [43]. We further showed that the YY1 C-terminal half which lacks the transcriptional activation domain is sufficient for controlling this loop [43].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation